Philosophy 167: Class 6 - Part 12 - Galileo's Key Postulate- Relating Vertical Fall to Fall Along Inclines. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Explains how Galileo used an incline plane to reach a conclusion about a vertical fall.; Opening line: "Now he wants to test it and he's got the problem, the problem I just demonstrated by dropping a coin."; Duration: 8:21 minutes.; Segment: Class 6, Part 12.